Geopolitical and Global Power Shift: The Economic, Military, and Political Rise of China in the 21st Century - Imam Zarkachi (Universitas Negeri Surabaya, 2023)
Abstract: The rise of China in the 21st Century is absolute, inevitable, and has been globally recognized. As the rising power in the international system, China has experienced significant economic growth, military capabilities development, and political involvement in the international setting. This study analyses the presence of China as a new great power is viewed as a threat to the United States’ hegemony, especially in the Asia region. China’s growing power will contest the US dominance in the region and drive the shift of major power both in the Asia region and the world. The study utilises a descriptive qualitative method with secondary data sources that were collected from books, journals, and other relevant resources. The findings from this study are China will continue to rise economically and become more aggressive militarily in dealing with international disputes, especially in the Asia region. Moreover, China has positioned itself as a central player in international stages such as the World Trade Centre (WTO) and the United Nations (UN) Peacekeeping. As a result, this rise is more likely to clash with the US as the sole superpower, and potential conflicts are unavoidable.